INTENSITAS PERILAKU MEROKOK REMAJA PUTRI DITINJAU DARI KONFORMITAS - Fahmi Islami; TA. Prapancha Hary (JURNAL SPIRITS, 2014)
ABSTRACTThis study aims to determine with more certainty on the smoking behavior of young women in terms of conformity, so as to provide an overview and map the sequence of events underlying the young women who smoke.Subjects in this study of young women aged 12-17 years who had a smoking behavior. This study used a single subject as a teenager and using a phenomenological approach, and using the techniques of data collection using interviews and observations.The research results of this study at the beginning of the subject smoking because seeing parents who smoke, when the subject of interest because the subject feels when parents smoke looks very calm and relaxed. So there is no effect of conformity, because the subject knows his friends when the subject had smoked.Â Keywords: Smoking Behavior, Young Women, Conformity